FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN NYERI PUNGGUNG BAWAH PADA ASN - Melvani, Rizcita Prilia (JURNAL KESEHATAN TERAPAN, 2021)
Background: Back pain is one of the main reasons for not working and every year millions of working days are lost due to back pain. Methods: This cross sectional study was conducted in 2020 with a sample of 52 ASN at the Regional Secretariat of OganKomeringIlir Regency using a simple random sampling technique. Data obtained through interviews using a questionnaire and analyzed univariate and bivariate using SPSS ver 25.0. Results: There is a significant relationship between BMI, length of sitting, and workload with LBP (p value = 0.008). Conclusion: There is a relationship between BMI, length of sitting, and workload with this LBP can be used as input to develop health services. Keywords: BMI, LBP, Length of Sitting, Workload